RELEVANCE BETWEEN PRINCIPLES OF USEFULNESS AND HUMANITARIAN PRINCIPLES IN A MUSLIM FRIENDLY TOURISM PERSPECTIVE - Nihayatul Maskuroh; Itang; Mukhlisotul Jannah; Elsa; Ratu Humaemah; M. Indrajit Roy; Surahman; Asep Dadan Suganda; Hadi Peristiwo (International Journal Mathla’ul Anwar of Halal Issues, 2022)
ABSTRACT The trend of Muslim friendly tourism is a new phenomenon in tourism. Judging from the principle of usefulness, the presence of Muslim friendly tourism provides a significant blessing to all parties involved in Muslim friendly tourism, especially in improving the economy. The demands of the Muslim community for a Muslim friendly tourism destination are not only limited to increasing the economy and the attractiveness of a tourist destination to Muslim friendly tourism, but also having an impact on the comfort factor and guarantees in carrying out worship are also part of Muslim friendly tourism which has basic value humanity. The purpose of this study is to identify and analyze the relationship between the principle of usefulness and humanitarian principles and their impact on Muslim friendly tourism. The research method used in this research is library research. The results of the study show that Muslim friendly tourism is a form of expression that the presence of Islamic law in the aspect of Muslim friendly tourism is rahmatan lil 'alamin which can provide the principle of benefit to stakeholders at large, and highly upholds the value of human principles and respects the existence of the form of human nature.